QUALITY OF SPECIALTY NATURAL COFFEE STORED IN DIFFERENT PACKAGES IN BRAZIL AND ABROAD - Borém, Flávio Meira; Andrade, Fabrício Teixeira; Santos, Cláudia Mendes Dos; Alves, Ana Paula de Carvalho; Matias, Gabriel Carvalho; Teixeira, Daniela Edel; Ossani, Paulo César; Cirillo, Marcelo Ângelo (Coffee Science - ISSN 1984-3909, 2019)
A challenge in the packaging and export of specialty coffees is to avoid green coffee bean storage and transport conditions that negatively affect the sensory quality of the roasted beans. This study evaluated green beans of specialty coffees in eight types of packaging storaged in in a warehouse in Poços de Caldas, MG, Brazil, for 18 months (Brazilian phase) and subject to sea transport and subsequent storage at a specialty coffee import company (export phase) in the United States, where it remained stored for 14 months. Physical, chemical, and sensory analyses of the beans were performed in the Brazilian phase and export phase. Green coffee beans stored in high-barrier packages had the best conserved quality. Packages with little or no barrier were not adequate for packaging or exporting of specialty coffees. Beans in high-barrier packaging maintained their quality for long periods, and this type of packaging is recommended for specialty coffee storage and export.